2021
DOI: 10.1177/00343552211006770
|View full text |Cite
|
Sign up to set email alerts
|

Testing Kumpfer’s Resilience Model Among Adults With Serious Mental Illness

Abstract: Having a serious mental illness (SMI) is often associated with significant adversities, and people respond differently to adversities. The existing research supports that people with SMI can achieve and maintain positive life outcomes despite experiencing adversities. Resilience, the ability to cope with (or bounce back quickly from) crisis, can help buffer the negative effects of various types of adversities, including chronic illness and disability, and facilitate the psychosocial adaptation process to SMI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 104 publications
(138 reference statements)
1
12
0
Order By: Relevance
“…The BFI-N was found to exhibit convergent validity by its strong positive correlation to the neuroticism subscale of the Five Factor Form ( r = .81), Five Factor Model Rating Form ( r = .81), and Ten Item Personality Inventory ( r = .81; Rojas & Widiger, 2014). Internal consistency of the neuroticism subscale has ranged between .77 and .87 in previous studies (John & Srivastava, 1999; John et al, 2008; Pan & Sánchez, 2022). The coefficient alpha was .77 in the current study.…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…The BFI-N was found to exhibit convergent validity by its strong positive correlation to the neuroticism subscale of the Five Factor Form ( r = .81), Five Factor Model Rating Form ( r = .81), and Ten Item Personality Inventory ( r = .81; Rojas & Widiger, 2014). Internal consistency of the neuroticism subscale has ranged between .77 and .87 in previous studies (John & Srivastava, 1999; John et al, 2008; Pan & Sánchez, 2022). The coefficient alpha was .77 in the current study.…”
Section: Methodsmentioning
confidence: 82%
“…We conducted a secondary analysis of data from a larger study (Pan & Sánchez, 2022). The original study aimed to validate a resilience framework among people with psychiatric disabilities and was approved by the Institutional Review Boards at The University of Iowa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it was also concluded that patients with SMI often do not receive evidence-based TFT ( 42 ). Unfortunately, resilience is still underestimated in outpatients with SMI ( 43 ) and also in patients with post-traumatic stress disorder ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] In addition, other researchers employed KRF to understand resilience in the face of diverse stressors in 32 studies, including 17 quantitative studies, 9 qualitative studies, 2 studies with mixed design, and 2 case studies. In these studies, KRF enabled researchers to examine the predictors and positive outcomes associated with resilience, 8,35,43,47 generate hypotheses for research questions, 3,6,9,28,36,37,44,46,49 understand and interpret the individuals' adaptation experience through the prism of KRF, * design targeted interventions to increase resilience, 39,45 develop new questionnaires to evaluate individuals' resilience, 32,43 and build disease-specific resilience models to understand resilience in concrete conditions. 4,5,[29][30][31] Thus, KRF is a useful theoretical framework with demonstrated efficacy across numerous studies.…”
Section: Step 4: Examining Usefulnessmentioning
confidence: 99%